The poetic teaching space: Gaston Bachelard and a third realm in management education. Issue 3 (4th July 2022) - Dahl, Matilda; Guillet de Monthoux, Pierre; Helin, Jenny
ABSTRACT: How to make students and teachers stop Stop and think and feel Reading slow Reading aloud Savouring silence Being there with all our emotions and bodies An experiment Not a social experiment Not a psychological experiment But a poetic Accompanied by a French philosopher Gaston Bachelard was always there in the atmosphere Our classroom practice With our master's students In sustainable management We searched for poetic moments Turned into a conversation Turned into a paper A paper about the poetics of teaching Phenomenologizing philosophy Rupturing classrooms